2008
DOI: 10.1016/j.nuclcard.2008.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Variability of myocardial ischemic responses to mental versus exercise or adenosine stress in patients with coronary artery disease

Abstract: Background-Mental stress precipitates myocardial ischemia in a significant percentage of Coronary Artery Disease (CAD) patients. Exercise or adenosine stresses produce different physiologic responses and cause myocardial ischemia via different mechanisms. Little is known about the comparative severity and location of myocardial ischemia provoked by these different stressors. In this study we sought to compare the within-individual ischemic responses to mental versus exercise or adenosine stress in a cohort of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…29,30 Interestingly, a recent study of CAD patients showed that mental stress provokes a different myocardial ischemic response compared to exercise or adenosine. 35 However, there is a little data available for patients groups with normal coronary arteries or syndrome X.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Interestingly, a recent study of CAD patients showed that mental stress provokes a different myocardial ischemic response compared to exercise or adenosine. 35 However, there is a little data available for patients groups with normal coronary arteries or syndrome X.…”
Section: Discussionmentioning
confidence: 99%
“…Its prognostic value is even more relevant, for in an analysis of 16 studies, with a total of 20,983 patients with normal radionuclide imaging and a mean follow-up of 28 months, a 0.7% rate of infarction or cardiac obit per year was observed, a value that is similar to the asymptomatic population 11 . Despite the excellent exactness of myocardial perfusion radionuclide imaging, some patients with established coronary disease 13 found a lower prevalence of ischemia during sensorial distress (19%), however, their criteria for ischemia were more rigid (SDS >4) than those of other studies 11 . Comparing the current study to the abovementioned ones, we observe that there is a higher prevalence of ischemia in our sample.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies demonstrate the difficulty in defining how patients respond to distress 2,13 . This limitation may be related to social factors or to natural alterations of the individual concerning his intrinsic capability of reacting to stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the most widely used exams, radionuclide imaging is the one that bespeaks the most its value in diagnostic and prognostic evaluation of patients with thoracic pain 1 . Despite the fact that a radionuclide myocardial perfusion imaging is frequently associated with a risk for adverse events lower than 1% per year 2 , some patients with coronary arterial disease only have manifestation of ischemia when submitted to non-conventional ischemia induction techniques, such as psychological stress 3 . While the basis for the induction mechanism for perfusion alteration of radionuclide imaging during physical activity with intravenous dipyridamole is coronary vasodilatation, psychological stress causes epicardial coronary and microvascular vasoconstriction in patients with endothelial dysfunction and/or arteriosclerosis 4 .…”
Section: Introductionmentioning
confidence: 99%